Japanese encephalitis virus expands regulatory T cells by increasing the expression of PD‐L1 on dendritic cells. Issue 5 (24th March 2014) - Gupta, Nimesh; Hegde, Pushpa; Lecerf, Maxime; Nain, Minu; Kaur, Manpreet; Kalia, Manjula; Vrati, Sudhanshu; Bayry, Jagadeesh; Lacroix‐Desmazes, Sébastien; Kaveri, Srini V.
<x xml:space="preserve">Abstract</x> The mechanisms underlying Japanese encephalitis virus (JEV) pathogenesis need to be thoroughly explored to delineate therapeutic approaches. It is believed that JEV manipulates the innate and adaptive compartments of the host's immune system to evade immune response and cross the blood–brain barrier. The present study was thus designed to investigate the functional modulation of DCs after exposure to JEV and to assess the consequences on CD4+ T‐lymphocyte functions. Human monocyte‐derived DCs were either infected with 1 MOI of live virus, UV‐inactivated virus, or were mock‐infected. Replication‐competent JEV induced a significant increase in the expression of maturation markers 48 h postinfection, along with that of programmed cell death 1 ligand 1 (PD‐L1; also called B7‐H1 and CD274). JEV‐infected DCs expanded the Treg cells in allogenic mixed lymphocyte reactions. The expansion of Treg cells by JEV‐infected DCs was significantly reduced upon blocking PD‐L1 using an antagonist. In addition, JEV‐infected DCs significantly altered the proliferation and reduced the polarization of Th cells toward the Th1‐cell phenotype. The results, for the first time, suggest that JEV evades the host's immune system by modulating the crosstalk between DCs and T lymphocytes via the PD‐L1 axis.